Public Health Spending, Governance Quality and Poverty Alleviation - Mohamad Komarudin; Mandar Oak (Economics and Finance in Indonesia, 2020)
Poverty alleviation has become the main priority program in most developing countries. This research empirically studies the correlation between public health spending, governance quality, and poverty alleviation in developing countries. The panel data were estimated via a random-effects (RE) model and robustness check using instrumental variables (IV) (two-stage least-squares [2SLS]) and first-difference generalized method of moments (GMM) because of the endogeneity problem. The results suggest that public health spending has a significant effect on reducing the poverty rate, and that countries with better governance tend to reduce poverty than countries with poor governance. Increasing public health spending by one percentage point may reduce poverty by 0.48 percentage points in countries with good governance supposing the governance quality influences public health spending. Conversely, in countries with poor governance, the poverty headcount ratio may decline by 1.375 percentage points when public health spending increases by one percentage point.